تطبيق القانون الأجنبي أمام القضاء الوطني - أسماء سالمي; عبير مجلاتي (My University, 2023)
Abstract : one of the key topics in private international law is the issue of conflict of laws, which presents various challenges, including how to apply foreign law before national courts ,jurisdiction is determined based on rules of allocation, and in such cases, the national judge must determine its nature, which can range from characterizing the factual situation to characterizing the law itself ,the nature of the case determines the burden of proof , either falling on the parties with an interest in its application, if the characterization focuses on the factual situation, or falling on the judge , who becomes bound to apply it automatically if the characterization focuses on the law the interpretation is then determined according to either the law of judge or the law of the foreign state, additionally, it is determined whether it is subject to the control of the supreme court, depending on whether it is considered as a law or a factual situation , the national judge has the discretion to it. ....................................................... ملخص : من أهم موضوعات القانون الدولي الخاص موضوع تنازع القوانين الذي يطرح إشكالات أهمها كيفية تطبيق القانون الأجنبي أمام القضاء الوطني، والذي ينعقد له الاختصاص بموجب قواعد الإسناد حيث أنه في هذه الحالة يتعين على القاضي الوطني تحديد طبيعته والتي تتأرجح بين وصف الواقعة والقانون، فطبيعته هي التي يتحدد على أساسها عبء الإثبات على من يقع ،فإذا أخذ وصف الواقعة هنا يقع على الخصوم أصحاب المصلحة الذين تمسكوا بتطبيقه أما إذا أخذ وصف القانون هنا يقع على القاضي ويصبح ملزما بتطبيقه تلقائيا، ويتحدد التفسير وفقا أي قانون يكون طبقا لقانون القاضي أم قانون الدولة الأجنبية، ويتحدد أيضا خضوعه لرقابة المحكمة العليا فإذا كان في منزلة القانون خضع لها أم إذا كان في منزلة الواقعة فلا يخضع لها ويمكن للقاضي الوطني استبعاد تطبيقه في حالة وجود أحد موانع الاستبعاد العامة أو الخاصة . ............................................................. Résumé l'un des sujets clés du droit international privé est la question du conflit de lois, qui présente divers défis, notamment comment appliquer le droit étranger devant les tribunaux nationaux, la compétence est déterminée sur la base de règles d'attribution, et dans de tels cas, le juge national doit déterminer sa nature, qui peut aller de la caractérisation de la situation de fait à la caractérisation du droit lui-même, la nature de l'affaire détermine la charge de la preuve, soit incombant aux parties ayant un intérêt à son application, si la qualification porte sur la situation de fait, ou incombant au juge , qui devient tenu de l'appliquer automatiquement si la qualification porte sur la loi l'interprétation est alors déterminée selon soit la loi du juge soit la loi de l'État étranger, en outre, il est déterminé si elle est soumise à le contrôle de la cour suprême, selon qu'il s'agit d'une situation de droit ou d'une situation de fait, le juge national y a toute discrétion.